MEMIMALISIR BULLYING DI PESANTREN TERPADU AL-FURQAN - Raiyan; Nelly Mursyidah; Syakbi; Nasrul Muzakkir (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
Bullying is a serious issue that occurs not only in public schools but also in pesantren, despite their focus on moral and religious values. This study aims to identify the types of bullying, its contributing factors, and the strategies implemented to address it at Pesantren Terpadu Al-Furqan. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that bullying in the pesantren encompasses verbal, social, and physical forms, driven by hierarchical seniority, a lack of awareness about the impacts of bullying, and differences in students' backgrounds. To address these issues, the pesantren has implemented strategies such as character education based on Islamic values, the formation of anti-bullying communities, strict supervision, psychological counseling services, and a confidential reporting system. These efforts have successfully created a more conducive environment by increasing students' awareness of mutual respect, improving social interactions, and reducing bullying cases. This study highlights the importance of a comprehensive approach to bullying prevention to establish a safe and supportive educational environment that fosters character development among students.